1980
DOI: 10.1063/1.91728
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxially grown monocrystalline garnet cathode-ray tube phosphor screens

Abstract: The technique of liquid phase epitaxy has been used to produce single-crystal garnet phosphor screens for cathode ray tubes. The films were rare-earth-doped yttrium aluminum garnets (YAG’s) grown onto YAG substrates using a PbO:B2O3 flux. We have studied the light output of these layers as a function of film growth temperature, rare-earth activator concentration, and incident power density. With Ce:YAG layers it was possible to use beam power densities up to 108 W/m2 and this produced a radiance of over 105 W/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Already in 1980 Robertson and van Tol demonstrated that epitaxial luminescent films of rare earth-doped garnets could withstand much higher power densities in cathode ray tubes without degradation than their powder counterparts (Robertson and Van Tol 1980). Since then, thin film phosphor materials have received significant attention (Choe et al 2001;Garskaite et al 2010).…”
Section: Thin Film Phosphorsmentioning
confidence: 99%
“…Already in 1980 Robertson and van Tol demonstrated that epitaxial luminescent films of rare earth-doped garnets could withstand much higher power densities in cathode ray tubes without degradation than their powder counterparts (Robertson and Van Tol 1980). Since then, thin film phosphor materials have received significant attention (Choe et al 2001;Garskaite et al 2010).…”
Section: Thin Film Phosphorsmentioning
confidence: 99%
“…The growth of LSO:Ce and (Lu 1-x Gd x ) 2 SiO 5 :Ce (LGSO:Ce) SCF scintillators onto LSO substrates by LPE method have been reported by some of us in [19,20] Testing the Lu 2 SiO 5 :Tb and Lu 2 SiO 5 :Tb,Ce SCF screens for visualization of X-ray image was performed as well [14]. The result of works [13,14] shows that the Lu 2 SiO 5 :Tb,Ce SCF screens with simultaneous emission in the blue and green ranges have excellent spatial resolution of X-ray image up to 0.8 μm FWHM [14].…”
Section: Introductionmentioning
confidence: 99%
“…During the last three decades the liquid phase epitaxy (LPE) proved to be a beneficial method for the development of luminescent materials based on single crystalline films (SCF) of oxide compounds, such as garnets, perovskites, sapphire, silicates and tungstates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Apart from the laser media [1], cathodoluminescent screens [2][3][4][5] and α-and β-scintillators [6][7][8], developed in the 80-90th of the last century on the base of rare-earth doped SCF of Y 3 Al 5 O 12 (YAG), Lu 3 Al 5 O 12 (LuAG) and Gd 3 Ga 5 O 12 (GGG) garnets, the application fields of such SCFs in the last decade are extended to X-ray visualization screens [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations